Use of Arabinonucleosides for Development and Implementation of a Novel 2′‐O‐Protecting Group for Efficient Solid‐Phase Synthesis and 2′‐O‐Deprotection of RNA Sequences. Issue 1 (14th January 2022) - Takahashi, Mayumi; Cawrse, Brian M.; Grajkowski, Andrzej; Beaucage, Serge L.
Abstract: The implementation of protecting groups for 2′‐hydroxyl function of ribonucleosides is very demanding in that synthetic RNA sequences must be highly pure to ensure the safety and efficacy of nucleic acid–based drugs for treatment of human diseases. A synthetic approach consisting of a condensation reaction between 2′‐ O ‐aminoribonucleosides with ethyl pyruvate has been employed to provide stable 2′‐ O ‐imino‐2‐methyl propanoic acid ethyl esters. Conversion of these esters to fully protected ribonucleoside phosphoramidite monomers has allowed rapid and efficient incorporation of 2′‐ O ‐protected ribonucleosides into RNA sequences while minimizing the formation of process‐related impurities during solid‐phase synthesis. Two chimeric 20‐mer RNA sequences have been synthesized and then exposed to a solution of sodium hydroxide to saponify the 2′‐ O ‐imino‐2‐methyl propanoic acid ethyl ester protecting groups to their sodium salts. When subjected to ion‐exchange conditions at 65°C and near neutral pH, fully deprotected RNA sequences are isolated without production of alkylating side‐products and/or formation of mutagenic nucleobase adducts. © 2022 Wiley Periodicals LLC. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Basic Protocol 1 : Synthesis of uridine 2′‐ O ‐imino‐2‐propanoic acid ethyl ester and its fully protected 3′‐ O ‐phosphoramidite Basic Protocol 2 : Synthesis of N 6 ‐protected adenosine 2′‐ O ‐imino‐2‐propanoic acid ethyl ester and its fully protected 3′‐ O ‐phosphoramidite Basic Protocol 3 : Synthesis of N 4 ‐protected cytidine 2′‐ O ‐imino‐2‐propanoic acid ethyl ester and its fully protected 3′‐ O ‐phosphoramidite Basic Protocol 4 : Synthesis of N 2 ‐protected guanosine 2′‐ O ‐imino‐2‐propanoic acid ethyl ester and its fully protected 3′‐ O ‐phosphoramidite Basic Protocol 5 : Automated solid‐phase RNA synthesis and deprotection using 2′‐ O ‐imino‐2‐proponate‐protected phosphoramidites